Cooperative Learning: Index Card Match Method in Increasing Students’ English Learning Outcome - Kisman; Nur, Rafi’ah; Ammade, Salasiah; Latifa, Ammang; Larekeng, Siti Hajar (JLE: Journal of Literate of English Education Study Program, 2024)
English language achievement encompasses proficiency in the English language, reflecting a person's ability to effectively comprehend, communicate, read, and write in English. The Index Card Method is a cooperative learning strategy that promotes active participation and collaboration in the classroom, encourages students to engage in active learning and develop their creativity. The aims of this research was to find out whether or not Index Card Match Method of cooperative learning can significantly increase students’ English achievement to the seventh grade students of SMP Negeri 6 Wonomulyo. The method used in this research is quantitative research using pre-experimental method with one group pre-test and post-test design. The procedure of collecting data involved administrating pre-test before treatment and post-test after treatment. The population of this research was seventh grade students of SMP Negeri 6 Wonomulyo academic year 2023/2024. The sample was taken by using cluster sample technique, where the researcher chose one class consisted 18 students. The result of this research showed that the mean score of students’ English achievement before taught by Index Card Match method was 38.89, while after doing the treatment, the mean score was 64.00. To find out the difference between pre-test and post-test, the researcher applied t-test. The value of t-test was 14.726 greater than the value of t-table 2.110 at the level of significance 0.05 and the degree of freedom was 17. The conclusion of this research is the Index Card Match method of cooperative learning can significantly increase the students’ English achievement.